Safety and efficacy of micropulse in pediatric eyes with refractory glaucoma - Sivasubramanian, Raajaraajeshwari; Siddharth, Kumar; Senthilkumar, Vijayalakshmi A; Mani, Iswarya; Rajendrababu, Sharmila (Indian journal of ophthalmology, 2025)
Purpose: To analyze the safety and efficacy of micropulse transscleral cyclophotocoagulation (MP-TSCPC) in pediatric eyes with refractory glaucoma. Design: Hospital-based prospective interventional study. Methods: Patients less than 18 years of age, receiving MP-TSCPC between December 1, 2022 and May 31, 2023 with at least three follow-ups within 6 months period, were included in the study. Post-laser evaluation was done at day 1, 1 month, 3 months, and 6 months. Success outcomes were calculated at 1, 3, and 6 months follow-up. Results: A total of 23 eyes of 23 patients were included in the study. Mean intraocular pressure (IOP) lowering agents (P = 0.041) had significant change compared to the baseline value; however, the change was insignificant when eyes requiring additional IOP-lowering surgeries during the follow-up period were excluded. There was a significant reduction in IOP at each follow-up visit compared to the baseline (P = 0.000014). Two (8.6%) eyes required additional intervention within 1-month follow-up, another six eyes (26%) between 1-3 months, and three eyes (13%) between 3-6 months of MP-TSCPC. Total success was highest at 56.5% (13 eyes) at 1-month follow-up and at least 34.7% (8 eyes) at 6-month follow-up. No major complications were reported in our study. Conclusion: MP-TSCPC was found to be safe and effective in pediatric population. However, we observed a gradual reduction in the success with time, and thus, it can be individualized to patients with high risk for incisional surgery or those requiring immediate IOP reduction.